INTEGRASI TERAPI SPIRITUAL AL-QUR'AN DAN PENGOBATAN NABI DALAM PENYEMBUHAN HOLISTIK: STUDI KONSEPTUAL OLEH REHAB HATI FOUNDATION - Isdianto, Andik; Al Indunissy, Nuruddin; Fitrianti, Novariza (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
The Qur'an is believed to have a healing dimension that is not only spiritual but also influences physical and mental health. This study examines the application of Quranic recitation-based therapy and Islamic medical practices as implemented by Rehab Hati Foundation. This research employs a qualitative method with a literature review approach to explore the concept of